Giant Pseudocyst of Spleen - D’Souza C; Rajashekar; Bhagavan K.R. (Journal of Clinical and Diagnostic Research, 2012)
False cysts of spleen or the pseudocysts accounts for about 75% of the non-parasitic splenic cysts and are usually traumatic in origin. These cysts are differentiated from the true cysts of the spleen by a absence of a epithelial layer on histology. We present here a case of a giant splenic pseudocyst in a young female with no previous history of trauma.